Enhanced immune response to foot-and-mouth disease vaccine by oral administration of ginseng stem-leaf saponins. (3rd July 2016) - Li, Renjun; Ma, Yanfen; Zhai, Lijuan; Lu, Yisong; Chi, Xiaoqing; Wu, Jiusheng; Hu, Songhua
Abstract: Vaccination is an important approach to the control of foot-and-mouth disease (FMD). This study evaluated the effect of oral administration of ginseng stem–leaf saponins (GSLS) on the immune response to FMD vaccine and the gut mucosal immunity in mice. In experiment 1, mice were orally administered GSLS or not treated as a control. The animals were then immunized twice with FMD vaccine. Blood was sampled weekly within five weeks after the boost immunization for measurement of serum IgG and the isotypes. In experiment 2, mice were orally administrated GSLS or not treated as a control. After that, splenocytes were prepared from sacrificed mice for lymphocyte proliferation assay and intestinal tissues were sampled for immunohistochemistry and histological examination. The results showed that oral administration of GSLS significantly enhanced serum IgG and the isotype responses to FMD vaccine as well as the number of intestinal intraepithelial lymphocytes (IELs) and immunoglobulin A (IgA)+ cells. Therefore, GSLS may be a potent oral adjuvant and deserve further study to improve vaccination in susceptible animals.